2016
DOI: 10.1097/md.0000000000005577
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of massive left atrial appendage thrombi with rivaroxaban before balloon mitral commissurotomy in severe mitral stenosis

Abstract: Rationale:Data on nonvitamin K antagonist oral anticoagulant being used for the treatment of LAA thrombi are limited only in nonvalvular atrial fibrillation. There are no data on the antithrombotic efficacy and safety of nonvitamin K antagonist oral anticoagulant in the resolution of left atrial appendage (LAA) thrombi in patients with rheumatic mitral stenosis.Patient concerns:A 49-year-old woman with known rheumatic mitral stenosis and atrial fibrillation was referred for percutaneous transvenous mitral comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Current guidelines recommend VKA therapy for LAA thrombus in patients with AF and the data regarding NOAC use for LAA thrombus in non‐valvular AF are limited to mainly case reports or case series. Use of VKA is limited by frequent INR checks prompting dose adjustment, compliance with certain diets, and hence NOACs provide some benefit with regard to reduced drug interactions and lack of need for coagulation monitoring 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current guidelines recommend VKA therapy for LAA thrombus in patients with AF and the data regarding NOAC use for LAA thrombus in non‐valvular AF are limited to mainly case reports or case series. Use of VKA is limited by frequent INR checks prompting dose adjustment, compliance with certain diets, and hence NOACs provide some benefit with regard to reduced drug interactions and lack of need for coagulation monitoring 8 …”
Section: Discussionmentioning
confidence: 99%
“…Use of VKA is limited by frequent INR checks prompting dose adjustment, compliance with certain diets, and hence NOACs provide some benefit with regard to reduced drug interactions and lack of need for coagulation monitoring. 8 In a retrospective study by Graham et al 9 Note: A study can be awarded a maximum of four stars for selection, two stars for comparability, and three stars for outcome.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a total of 14 studies [14][15][16] have reported the use of all types of NOAC, including rivaroxaban, for the resolution of LAA thrombus in patients with non-valvular AF in whom previous anticoagulation was ineffective. These studies generally indicated beneficial results -the change of anticoagulant agent resulted in resolution of thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…These studies generally indicated beneficial results -the change of anticoagulant agent resulted in resolution of thrombus. However, most of these studied are case reports and only standard doses of anticoagulants were used [15,16]. Three case reports demonstrated resolution of thrombus in the LAA during rivaroxaban once a day therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Обращает на себя внимание даже сообщение Li Y. и соавт. об успешном использовании ППОАК ривароксабана при тромбозе ушка ЛП у пациентки с митральным стенозом ревматической этиологии [39].…”
Section: Discussionunclassified